(untitled) (Medical Forum Monthly, 2024)
Objective: To diagnose different conditions producing pancytopenia on the basis of clinical, hematological and bone marrow studies. Study Design: Prospective Study Place and Duration of Study: This study was conducted at the Department of Medicine, Saidu Teaching Hospital, Saidu Sharif, Swat from March 2011 to March 2012. Materials and Methods: 100 patients with pancytopenia were analyzed. Peripheral smears of the patients were analyzed for RBC, WBC and platelets morphology along with presence and absence of immature cells and abnormal cells. On bone marrow examination, morphology of all cells lineage, cellularity, parasite and abnormal cells were scrutinized. Trephine biopsy was done where ever indicated Results: Patients age ranging from 12 to 80 years. Most of the patients (70%) were in the 12-30 years of age group. Pallor was the predominant clinical feature (97%) while weakness was the main presenting feature (71%). Aplastic anemia (42%) followed by Megaloblastic anemia (28 %) was found to be the most common cause of pancytopenia as unveiled by bone marrow examination Conclusion: In Swat, the prevalent causes of pancytopenia are Aplastic anemia, Acute leukemia, Megaloblastic anemia and Hypersplenism.